Synthesis A.nd Study The Biological Activity of Some Schiff-Bases Derived F,rom 2- Aminothiazole or 2-Aminobenzothiazole and Vanillin Derivatives - Afi, E. T.; Tomma, J. H.; Mubbr k, S. S. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
Two  series    of   1,n-alkylene    glycol   di [4{N(T-thiazolylazoÂnrethinyl)}2-metho y]     phenyl     ether     and     I ,n-alkylene      glycol di[4{N(r-benzo-thiazolylazomethinyl)}2-methoxy]phenyl ether were synthesize-d via rea tions  2-aminothiazole and  2-aminobenzothiazole with  dialdehyde â€¢ (which  are synthesized  from  .reaction  vanil.lin withl ,n-dibromo   or   ehloro.   alkane   in  the   basic   me'dia   )   .   The   newcompounds characterized by elemental  analysis  (of some  of theme)  , physical  and spectral  data .All the schiff-bases have been screened  for their antifungal  and antibacterial  activity against Aspergillus niger ,. Escherichi    coli    (0-)  and    Staphylococcus   aureus   . (G+)   .  AlJ compounds  were  found   to  be  active   antibacterial and   antifungal (except [III] 12 was not show any antifungal  activity).